Perubahan Kelarutan Protein, Kandungan Lisin (Available), Metionin dan Histidin Bandeng Presto Selama Penyimpanan dan Pemasakan Ulang - Suwedo Hadiwiyoto; Sri Naruki; Sri Satyanti; Hastini Rahayu; Diana Riptakasari (agriTECH, 1999)
"Bandeng presto" is a product made by pressure cooking of fresh milkfish (Chanos chanos). Before it is consumed generally stored at low temperature (0-4Â°C), after that it is recooked by steaming or deep frying. During low temperature storage the solubility of protein decreased but there was no change in isoelectric zone found at pH 5-6 based on the solubility patern data, which is showed a structural changes on protein molecules. Decreasing on the content of available lysine, methinone, and histidin during storage was obtained as a function of time but they were not significant. Recoldng by steaming and deep frying reduced contents of those amino acids to the level lower than amino acid pattern recomended by FAO/WHO. Decreasing of available lysine, methionine, and histidin was found higher by frying than those by steaming.